Quantifying the Association between Campylobacter Infection and Guillain-Barré Syndrome: A Systematic Review - Poropatich, Kate O; Fischer Walker, Christa L; Black, Robert E (Journal of Health, Population and Nutrition, 2010)
Guillain-Barré Syndrome (GBS) is a neurologic disease that causes ascending paralysis and is triggered by a preceding bacterial or viral infection. Several studies have shown that patients with GBS have a recent history of infection due to Campylobacter jejuni. A literature review of published studies that reported rates of Campylobacter infection before or in conjunction with GBS was done. These reported data were used for calculating the proportion of GBS cases who tested positive for Campylobacter compared to the control population and the incidence of GBS among patients infected with Campylobacter. Results of the analysis suggest that 31% of 2,502 GBS cases included in these papers are attributable to Campylobacter infection. Key words: Campylobacter; Campylobacter infections; Guillain-Barré Syndrome; Review literature DOI: 10.3329/jhpn.v28i6.6602 J HEALTH POPUL NUTR 2010 Dec;28(6):545-552